Innovation and Institutional Ownership - Aghion, Philippe; Van Reenen, John; Zingales, Luigi (American Economic Review, 2013)
We find that greater institutional ownership is associated with more innovation. To explore the mechanism, we contrast the “lazy manager” hypothesis with a model where institutional owners increase innovation incentives through reducing career risks. The evidence favors career concerns. First, we find complementarity between institutional ownership and product market competition, whereas the lazy manager hypothesis predicts substitution. Second, CEOs are less likely to be fired in the face of profit downturns when institutional ownership is higher. Finally, using instrumental variables, policy changes, and disaggregating by type of institutional owner, we argue that the effect of institutions on innovation is causal. (JEL G23, G32, L25, M10, O31, O34)